Plasma proteome plus site‐specific N‐glycoprofiling for hepatobiliary carcinomas - Ting‐Tsung Chang; Ji‐Hong Cheng; Hung‐Wen Tsai; Kung‐Chia Young; Sun‐Yuan Hsieh; Cheng‐Hsun Ho (Wiley, 2019)
Abstract Hepatobiliary cancer is the third leading cause of cancer death worldwide. Appropriate markers for early diagnosis, monitoring of disease progression, and prediction of postsurgical outcome are still lacking. As the majority of circulating N‐glycoproteins are originated from the hepatobiliary system, we sought to explore new markers by assessing the dynamics of N‐glycoproteome in plasma samples from patients with hepatocellular carcinoma (HCC), cholangiocarcinoma (CCA), or combined HCC and CCA (cHCC‐CCA). Using a mass spectrometry‐based quantitative proteomic approach, we found that 57 of 5358 identified plasma proteins were differentially expressed in hepatobiliary cancers. The levels of four essential proteins, including complement C3 and apolipoprotein C‐III in HCC, galectin‐3‐binding protein in CCA, and 72 kDa inositol polyphosphate 5‐phosphatase in cHCC‐CCA, were highly correlated with tumor stage, tumor grade, recurrence‐free survival, and overall survival. Postproteomic site‐specific N‐glycan analyses showed that human complement C3 bears high‐mannose and hybrid glycoforms rather than complex glycoforms at Asn85. The abundance of complement C3 with mannose‐5 or mannose‐6 glycoform at Asn85 was associated with HCC tumor grade. Furthermore, stepwise Cox regression analyses revealed that HCC patients with a hybrid glycoform at Asn85 of complement C3 had a lower postsurgery tumor recurrence rate or mortality rate than those with a low amount of complement C3 protein. In conclusion, our data show that particular plasma N‐glycoproteins with specific N‐glycan compositions could be potential noninvasive markers to evaluate oncological status and prognosis of hepatobiliary cancers.